If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3x-3)=2x+22
We move all terms to the left:
2(3x-3)-(2x+22)=0
We multiply parentheses
6x-(2x+22)-6=0
We get rid of parentheses
6x-2x-22-6=0
We add all the numbers together, and all the variables
4x-28=0
We move all terms containing x to the left, all other terms to the right
4x=28
x=28/4
x=7
| 2(5x+3)=22 | | 7x-4^2+19^2=10x+3^2 | | x+x^2=52 | | 2x+10=-3x-25 | | 2x-10=-3x-25 | | 16+10x=8x–2 | | x/0.7=40 | | x^2-x-7/4=0 | | X-y=87 | | 18y-60=-20 | | 7x—1=3x+7 | | 12/63=27n | | 0=x^2-56x+384 | | 3(9x+7)=27 | | 35/12=14n | | 2y−4=9 | | 24/30=20n | | 4/42=14n | | 0=x^2+10x-1200 | | 5(x-3=20 | | 14/63=49n | | 30x–3=27 | | 12/125=30n | | 0=x^2+5x+1800 | | 1/3x-2=2/x-5 | | 20/21=14n | | 1-3x=-6+4 | | 3m-6=m/2+1/3 | | 4x+6=9x+10 | | 40/63=36n | | 42-4x-2=50 | | 12/45=54n |